Bildgestützte Strahlentherapie: Paradigmenwechsel in der Strahlentherapie = Image-guided radiation therapy : paradigm change in radiation therapySchönberg - Wenz, Frederik; Schönberg, Stefan (Der Radiologe, 2012)
Clinical issueThe introduction of image-guided radiotherapy (IGRT) has changed the workflow in radiation oncology more dramatically than any other innovation in the last decades.Standard treatmentImaging for treatment planning before the initiation of the radiotherapy series does not take alterations in patient anatomy and organ movement into account.Treatment innovationsThe principle of IGRT is the temporal and spatial connection of imaging in the treatment position immediately before radiation treatment.Diagnostic assessmentThe actual position and the target position are compared using cone-beam computed tomography (CT) or stereotactic ultrasound.PerformanceThe IGRT procedure allows a reduction of the safety margins and dose to normal tissue without an increase in risk of local recurrence.AchievementsIn the future the linear treatment chain in radiation oncology will be developed based on the closed-loop feedback principle.Practical recommendationsThe IGRT procedure is increasingly being used especially for high precision radiotherapy, e.g. for prostate or brain tumors.
Paralleltitel von Frontdoor übernommen
Gesehen am 23.11.2018